Foreign employment for women challenges & opportunities : a collection of articles published during the media campaign - Sangraula, Lok Nath.; Sancharika Samuha (Nepal).; United Nations Development Fund for Women (Lalitpur Sancharika Samuha Kathmandu UNIFEM, 2003)
Contributed articles on employment of Nepali women in foreign countries.
Keywords: Women -- Employment -- Nepal -- Foreign countries